1995
DOI: 10.1001/jama.1995.03520420055038
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion Requirements in Critical Care

Abstract: In this small randomized trial, neither mortality nor the development of organ dysfunction was affected by the transfusion strategy, which suggests that a more restrictive approach to the transfusion of RBCs may be safe in critically ill patients. However, the study lacked power to detect small but clinically significant differences. Therefore, further investigations of RBC transfusion strategies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(28 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…The mortality rate in our study was slightly higher than that reported in the TRICC study but similar to other previous reports [11,21]. Mortality rates differed significantly by organ failure, consistent with previous reports [1].…”
Section: Discussionsupporting
confidence: 92%
“…The mortality rate in our study was slightly higher than that reported in the TRICC study but similar to other previous reports [11,21]. Mortality rates differed significantly by organ failure, consistent with previous reports [1].…”
Section: Discussionsupporting
confidence: 92%
“…3 We know of only 5 randomized clinical trials, including a total of 207 patients, that have contrasted transfusion triggers. [4][5][6][7][8] No differences in mortality or morbidity were found between high and low transfusion thresholds. However, even collectively, these trials followed too few patients to evaluate the effect of lower transfusion triggers on clinically important outcomes.…”
mentioning
confidence: 99%
“…Leukocytes from donated blood may play a key role in immune system suppression; however, the exact mechanism is unclear [ 47 ]. Studies had reported a decrease in mortality rate among patients receiving prestorage leukoreduced blood compared to patients receiving nonfiltered blood [ 22 , 23 ]; however, a meta-analysis of 12 RCTs comparing leukodepleted and nonleukodepleted RBCs failed to identify an association between leukoreduction and mortality (OR 1.14, 95%CI, 0.89 to 1.45) [ 48 ]. Of the eighteen studies included in our review, only seven of them had information on percentage of patients receiving nonfiltered blood.…”
Section: Discussionmentioning
confidence: 99%
“…and Hebert et al . had reported decreased mortality among patients receiving prestorage leukoreduced blood compared to patients receiving nonfiltered blood [ 22 , 23 ], indicating that leukocytes from donated blood may be crucial in the development of immune system suppression. Another transfusion practice is using ‘fresh’ transfused RBCs instead of ‘old’ blood; some studies suggested that the use of old stored RBCs is a potential risk factor for mortality [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%